Cyclists fatalities: Forensic remarks regarding 335 cases. (November 2016) - Piras, M.; Russo, M.C.; De Ferrari, F.; Verzeletti, A.
Abstract: A retrospective study was carried out on post-mortem examination data regarding 335 cyclists involved in fatal accidents along the period 1983–2012. The following variables were considered: temporal data (year, month, day of the week and hour of the day), circumstances of the accident, vehicles involved, victims' features (sex, age), pathological and toxicological findings, cause of death. Most victims were male (77.62%), with a mean age of 58 years. In most cases vehicles other than only bicycles were involved, more frequently cars, followed by heavy motor vehicles. Head was the most frequently body region involved in lethal injuries (65.37%); low extremities were the body district most frequently involved in non-lethal injuries (63.9%). This study confirmed the importance of using helmet; head protection should be a priority for bikers. Highlights: Fatal traffic accidents involving cyclists are frequent and the main cause of death is head injuries. Epidemiological and pathological data in cyclists' accidents are available, but few regarding the Italian context. The use of helmet has to be promoted.